2022
DOI: 10.3390/app122312294
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Poultry Litter and Its Biochar on Soil Fertility and Jatropha curcas L. Growth on Sandy-Loam Soil

Abstract: Low agricultural output and a decline in plant-available nutrient content in soil pose significant challenges to developing countries. To test the hypothesis that poultry litter and its biochar improve soil quality, nutrient status, and plant growth, a greenhouse pot experiment with sandy-loam soil was conducted. Selected application rates of poultry litter (0, 15, 30, 60, and 120 g/kg) and its biochar pyrolyzed at 350 °C and 600 °C were used. With the addition of organic amendments, Jatropha plant height, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…According to Bade et al [16], it also has higher levels of NPK than other kinds of manures. This manure can increase the soil's organic matter content, microbial activity, anion and cation exchange capacity, and carbon content [17]. This work was designed to assess the effects of chicken manure levels on sweet pepper types' yield and capsaicicoid content in an effort to improve the development of capsicum varieties with high capsaicin content.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bade et al [16], it also has higher levels of NPK than other kinds of manures. This manure can increase the soil's organic matter content, microbial activity, anion and cation exchange capacity, and carbon content [17]. This work was designed to assess the effects of chicken manure levels on sweet pepper types' yield and capsaicicoid content in an effort to improve the development of capsicum varieties with high capsaicin content.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kimani et al showed that poultry litter biochar increases rice yield and nitrogen use efficiency 17 . Also, positive effects of manure-derived biochar on the growth of lettuce, cherry tomato, maize, bean and Jatropha curcas were reported 10 , 18 20 . However, a potential drawback of biochar addition is the accumulation of toxic compounds like polycyclic aromatic hydrocarbons (PAHs) and potentially toxic elements (PTEs; Pb, Cd, Cu, Ni, Hg, Zn, Cr and As) in the soil 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The poultry litter composting process [11] transforms the soluble nutrients into stable organic forms [12]. In addition, aerobic treatment reduces the waste moisture content [13]. To obtain the organic fertilizer used for soil fertilization [14], both poultry waste [15] and manure [16] can be composted.…”
Section: Introductionmentioning
confidence: 99%